(untitled) (Baghdad Science Journal, 2011)
This study Achieved to search form the infections by Cholera and Diarrhea in two different areas from the side of Cultural, Social, Economical and Environmental field in Baghdad governorate, during a period from 3/10 – 3/12/2007.these were in Obiady city and Palestine street. This study included groups of patients who went to the Kindy Hospital lab. The researcher use a sample of (300) persons of different ages with range (150) persons in each city from the study city, in this study show a great different in the percentage of infection by parasites, helminthes, viruses, bacteria and vibrio cholera in the two city according to age groups, reach upper percentage by infection in age (1-10) years in Obiady city with percent (57.5 %) while was in Palestine street (16.62%) and was the infection in age group (31-40) years reach (75%) in Odiady city in comparison with Palestine street that reach ( 7.40 %) due to differences of the Economical and Environmental and Increasing service supports in Palestine street comparing with Obiady city .